Implementation of The Integrated Curriculum of Faculty of Dentistry Universitas Indonesia - Antonia Tanzil; Safrida Hoesin; Margaretha Suharsini; M. Siagian; D. I. Soeria Santoso (Faculty of Dentistry, Universitas Indonesia, 2013)
Since the last five years, Faculty of Dentistry Universitas Indonesia has implemented an integrated curriculum as a process of change from teacher centered to student centered learning, as well as problem based learning, community based and praciticing in a small group discussion. The dental curriculum is divided separately into seven semesters for academic and followed by three semesters for clinical years. The aim of this study is to evaluare the implementation of the integrated curriculum. Evaluation of this five year program showed less than 10% of the 5th year students were able to finish their study on time. Most of the students needed more than three semesters to complete the clinical requirements; therefore, the recent curriculum should be revised. DOI: 10.14693/jdi.v16i2.93